2020
DOI: 10.1080/23802359.2020.1746207
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of the Japanese rock ptarmigan (Lagopus muta japonica Clark, 1907)

Abstract: The rock ptarmigan Lagopus muta is a grouse widely distributed in the arctic and subarctic regions of Eurasia and North America. The range of Japanese endemic subspecies (Japanese rock ptarmigans: L. m. japonica) is the southernmost of this species, but their origin is little known. Here, we determined the complete mitogenome of this subspecies and carried out the phylogenetic analysis. It was demonstrated that Japanese rock ptarmigans are old divergent lineage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…The mitochondrial DNA was described with all 13 expected protein coding regions and analyzed for accuracy through comparative analysis. With our addition, there are now four extant mitochondrial genomes published for the Rock Ptarmigan; Two from Iceland, one from Japan, and one from Siberia (Sveinsdóttir and Magnússon, 2017; Yonezawa and Nishibori, 2020; Wang et. al., 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mitochondrial DNA was described with all 13 expected protein coding regions and analyzed for accuracy through comparative analysis. With our addition, there are now four extant mitochondrial genomes published for the Rock Ptarmigan; Two from Iceland, one from Japan, and one from Siberia (Sveinsdóttir and Magnússon, 2017; Yonezawa and Nishibori, 2020; Wang et. al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The mitochondrial genome was assembled separately from both raw reads and contigs using MitoHifi (v. 2.2; Uliano-Silva et. al., 2021) with automatic alignment to the Japanese Rock Ptarmigan ( L. muta japonica; Yonezawa and Nishibori, 2020) via built-in features from the MitoFinder dependency (v. 1.4.1; Allio et. al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The mitochondrial DNA was described with all 13 expected protein-coding regions and analyzed for accuracy through comparative analysis. With our addition, there are now four extant mitochondrial genomes published for the Rock Ptarmigan; two from Iceland, one from Japan, and one from Siberia ( Sveinsdóttir and Magnússon 2017 ; Wang et al 2017 ; Yonezawa and Nishibori 2020 ). Using the ClustalW package embedded in BioEdit ( Thompson et al 1994 ; Hall 1999 ), we found a total of 24 bases divergent from the previously published Icelandic Rock Ptarmigan mitogenome in a manual review.…”
Section: Resultsmentioning
confidence: 99%
“…The mitochondrial genome was assembled separately from both raw reads and contigs using MitoHifi (v. 2.2; Uliano-Silva et al 2021 ) with automatic alignment to the Japanese Rock Ptarmigan ( L. muta japonica ; Yonezawa and Nishibori 2020 ) via built-in features from the MitoFinder dependency (v. 1.4.1; Allio et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…These updated phylogenies provide new insights into the origins and history of domestication. With the aim of addressing these questions for Tosa-Jidori, we selected one sample (Tosa 2; 921 strain) for determination of the complete mitogenome sequence as described by other researchers using different bird species (Japanese quail [ 16 ]; chickens [ 17 , 19 , 23 ]; rock ptarmigans [ 24 ]).…”
Section: Resultsmentioning
confidence: 99%